The suppression of lithium dendrite growth in lithium sulfur batteries: A review. (October 2017) - Xu, XiaoLong; Wang, SuiJun; Wang, Hao; Xu, Bin; Hu, Chen; Jin, Yi; Liu, JingBing; Yan, Hui
Highlights: We review the recent progresses of the lithium dendrite suppression in LSBs. Modifications of anode and electrolyte are used in improving safety of LSB anodes. Electrolyte additive suppresses dendrite by modifying electrolyte/anode interface. Seeking the novel separator with 3D structure will be a new route. Abstract: Lithium sulfur batteries (LSBs) are attractive owing to the high theoretical capacities of sulfur cathode active material (1672 mAh g −1 ) and lithium anode active material (3862 mAh g −1 ), which leads to a specific energy of approximately 2600 Wh kg −1 . However, for any rechargeable batteries employing lithium metal as the anode, a major failure mechanism is uncontrolled dendrite formation, which presents serious safety issues, low Coulombic efficiency and poor cycle performance. Recently, researchers make great effort to overcome these problems. Here we summarize some methods for suppressing lithium dendrite growth based on the failure mechanism of LSBs, mainly including novel separator, anode modification and electrolyte modification. We also discuss the advantages and disadvantages of different methods and point out the challenges that still needed to be addressed for building better LSBs.